Natural Language Processing for Electronic Design Automation - Soeken, Mathias; Drechsler, Rolf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book describes approaches for integrating more automation to the early stages of EDA design flows. Readers will learn how natural language processing techniques can be utilized during early design stages, in order to automate the requirements engineering process and the translation of natural language specifications into formal descriptions. This book brings together leading experts to explain the state-of-the-art in natural language processing, enabling designers to integrate these techniques into algorithms, through existing frameworks. Serves as a single-source reference to natural language processing for electronic design automation; Provides techniques that can be used without a deep understanding of computer linguistics; Includes illustrative examples that make it easy to apply the techniques presented to the reader$1 (Bs own design flow.s
Chapter 1. (Semi-)Automatic Translation of Legal Regulations to Formal Representations: Expanding the Horizon of EDA Applications -- Chapter 2. Semi-Formalization of Requirements for Analog/Mixed-Signal Products with Application in Automotive Domain -- Chapter 3. Generation of Verification Artifacts from Natural Language Descriptions -- Chapter 4. Real-world Events Discovering with TWIST.
Keywords: Physics; Electronic circuits; Electronics; Microelectronics; Computer-aided engineering; Applied and Technical Physics; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Computer-Aided Engineering (CAD, CAE) and Design